De nøgne kvinder i hammam: paradis eller helvede? - Østergaard, Kate (Kvinder, Køn & Forskning, 2000)
The article focuses on the gendered discussions of the public bathhouses i Marocco, also called hammam. Hammam in Casablanca is a necessity and a local practice for the low income sections of the population, and for women it functions as a social meetingplace. Likewise it is legitimized as a religious practice, but is at the same time being associated with shamelessness according to theological discussions.